Pengaruh Aksesibilitas dan Karakteristik Sosial Ekonomi Terhadap Mobilitas Masyarakat (Studi Kasus di Kecamatan Tanjung Karang Pusat Kota Bandar Lampung) - Randy Setiawan (Rekayasa : Jurnal Ilmiah Fakultas Teknik Universitas Lampung, 2019)
The purpose of this study is analyze the correlation of accessibility to the level of mobility and the correlation of mobility to socio-economic in Tanjung Karang Pusat sub-district. The sample targets are the people in Tanjung Karang Pusat sub-district as well as from the competent parties in their field, using the random sampling technique. Data collection is done through questioner with descriptive analysis method and PSPP analysis. Based on the calculation of IRI (index of road infrastructure) value in Tanjung Karang Pusat sub district, which is 5.74, the value almost meets the national minimum value requirement, which is 6. For accessibility index is 22,289 larger than MSS (>5,0) while for mobility index has a value of 1.355 smaller than MSS (minimum service standard) requirements that have been set which is > 2.0. The level of mobility is strongly influenced by the regional income itself. One way to increase the IRI value is by adding a road network. The writer took Durian Payung urban village which has a lot of vacant land area, which is increase 3.91 km and able to raise IRI to become 6,01 and exceed national minimum value. In correlating the mobility with the socioeconomic obtained the equation f(x) = 2,71+0,25X1+0,04X2+0,12X3+0,14X4 based on T-test the influential value is income. Correlation of accesability with mobility obtained the equation f(x) = 1,64+0,004X1+0,37X2+0,0002X3 based on T-test the influential value is travel destination . Correlation of accesability and socioeconomic with mobility obtained the equation f(x) = 2,12+0,11X1+0,03X2 based on T-test the influential value is accesability. Key words: Accesability, Mobility, Socioeconomic, Tanjung Karang Pusat